ORAL INTAKE OF SARDINELLA LONGICEPS OIL THE DECREASE OF TNF-? AND IL-6 LEVELS IN ATHEROSCLEROTIC WISTAR RAT - Wahjuni, S.; Sudewa, A.A.G.; Wita, I Wayan; Astawa, I.N. Mantik (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES; Vol. 5, No. 2 Mei 2011)
Lifestyle changes to consumption of variegated instant food may be associated several heath hazards, such as obesity, dyslipidemia, and atheroschlerosis. This study was conducted to investigate the effects of orally administered Sardinella longiceps oil as an anti inflammatory agent on the serum levels of TNF-? and IL-6 considered as biomarkers for atherosclerosis.The study design is an true experimental with randomized pretest and posttest control group design, using 50 Wistar rat equaly divided into 5 groups, i.e. placebo control group 0% and 4 treatment groups each treated daily with 10%, 15 %, 20 % and 25 % fish oil respectively for 6 weeks. Before the treatment was started, all rats were orally fed daily with a high cholesterol diet for 13 weeks to induce atherosclerosis. Our study showed that the intake of 20% fish oil had resulted in the significantly greatest decrease of 45,63 % in the TNF-? serum levels,from 28.62 ± 1.25 to 15.56 ± 7.20 ?g/mL and similar significant decrease 15,42% in of IL-6 serum levels from 134.64 ± 1.98 to 113.87 ± 4.30 ?g/mL. The overall results of our study seemed to imply than in the Wistar rats, oral intake of Sardfinella longiceps oils signifacantly decreased serum levels of TNF-? and IL-6 probably through their anti-inflamatory effects. Futher research to determin the magnitude of effects sardinella longiceps oils on the serum levels TNF-? and IL-6 human.
Keywords: Sardinella longiceps oils, fish oils, anti-inflammatory agent, lifestyle changes. Instant foods, TNF-? and IL-6 in human.